The relationship between quality of life, sleep quality, mental health, and physical activity in an international sample of college students: a structural equation modeling approach - Imen Moussa-Chamari; Imen Moussa-Chamari; Abdulaziz Farooq; Mohamed Romdhani; Mohamed Romdhani; Jad Adrian Washif; Ummukulthoum Bakare; Mai Helmy; Ramzi A. Al-Horani; Paul Salamh; Nicolas Robin; Olivier Hue (Frontiers Media S.A., 2024)
ObjectiveWe assessed the direct and indirect relationships between sleep quality, mental health, and physical activity with quality of life (QOL) in college and university students.MethodsIn a cross-sectional design, 3,380 college students (60% females; age = 22.7 ± 5.4) from four continents (Africa: 32%; America: 5%; Asia: 46%; and Europe: 15%; others: 2%) completed the Pittsburgh Sleep Quality Index (PSQI); Insomnia Severity Index (ISI); Epworth Sleepiness Scale (ESS); the Depression, Anxiety, and Stress Scale 21 (DASS); the International Physical Activity Questionnaire short-form (IPAQ); and the World Health Organization Quality of Life-BREF (WHOQOL-Brief).ResultsWe showed that sleep quality, insomnia, and depression had direct negative effects on the physical domain of QOL (β = −0.22, −0.19, −0.31, respectively, p < 0.001). There was a strong negative direct association between depression and the psychological domain of QOL (β = −0.60, z = −22.21, p < 0.001). Both stress and PSQI had direct effects on social relationships QOL (β = 0.11; z = 4.09; and β = −0.13; z = −7.40, respectively, p < 0.001). However, depression had the strongest direct impact on social relationships QOL (β = −0.41, z = −15.79, p < 0.001).ConclusionThe overall QOL of university students is associated with their sleep quality, mental health, and physical activity warranting further interventional studies aiming at improving students' quality of life.